Korupsi di Badan Usaha Milik Negara Khususnya Perusahaan Perseroan: Suatu Kajian atas Makna Kekayaan Negara yang Dipisahkan dan Keuangan Negara - Ridwan Khairandy (Fakultas Hukum Universitas Islam Indonesia, 2009)
This article seek to discuss the concept of the state’s properties which are included in the state enterprises (BUMN), especially those which are in the form limited liability companies (Persero). From legal perspective, state’s properties which are placed in a limited liability companies are separated properties. The inclusion of such properties in a limited liability company brings about a legal consequence, namely, such properties are then legally belong to the company instead of the state. A limited liability company is an independent entity, and hence, physically, the said state’s properties are then deemed as the share. It suffices to conclude therefore, that the statecan not in any way in possession of the company as a whole, but rather merely on the limited amount of share.